50 literacy strategies : step by step - Tompkins, Gail E. (Pearson Education, 2013)
"The new edition of 50 Literacy Strategies: Step by Step refocuses the strategies to provide clearer guidance for adapting practices for all learners and integrating technology and standards. As always, everything you need to know to implement teach instructional strategy - including appropriate grade range, the when and why to use the strategy, and step by step descriptions - is here in a consistent, easy-to-understand format."--Publisher's website.